Secure Transmission Based on Antenna Selection for Network Coding System - Dan Deng; Ming Zhao; Guizhou Jian (Dianxin kexue)
In order to improve the secrecy capacity of analog network coding system, antenna selection based transmission scheme was investigated. The selection criteria for the source nodes and relay nodes were proposed over a slowly varying channel. The optimal selection criterion for maximum secrecy capacity and the suboptimal selection criterion for maximum channel gain ware investigated. Simulation results show that the selection scheme of combined main channel capacity maximum（CMCCM）outperforms other schemes with the most computation burden. Compared with the fixed selection, the proposed scheme shows about 5 dB gain in ergodic secrecy capacity. Specifically, the independent channel gain maximum（ICGM）scheme holds the similar performance compared with CMCCM scheme, while ICGM scheme can release the computation burden.